'It isn't "help, " it's work': Legal regulation of domestic work in Bangladesh. (December 2018) - Rahim, Mia Mahmudur; Islam, Sk Samidul
Although many households in Bangladesh employ domestic workers, these workers remain outside any legal regulation framework. By evaluating the country's legal context, this article reveals that existing legal provisions for domestic work are extremely limited and insufficiently safeguard workers' rights. A new regulation is necessary; this article details the essentials of such legislation. The proposed legislation involves a stakeholder initiative to transform the existing manipulative dependency relationship to a more equitable relationship between the domestic workers and their employers.